2001
DOI: 10.1099/00221287-147-3-653
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a copper-transport operon, copYAZ, from Streptococcus mutans The GenBank accession number for the cop operon sequence reported in this paper is AF296446.

Abstract: A copper-transport (copYAZ) operon was cloned from the oral bacterium Streptococcus mutans JH1005. DNA sequencing showed that the operon contained three genes (copY, copA and copZ), which were flanked by a single promoter and a factor-independent terminator. copY encoded a small protein of 147 aa with a heavy-metal-binding motif (CXCX 4 CXC) at the C-terminus. CopY shared extensive homology with other bacterial negative transcriptional regulators. copA encoded a 742 aa protein that shared extensive homology wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 34 publications
2
54
0
Order By: Relevance
“…The residues Cys-207 and Cys-210, which belong to a CXXC metal binding motif, are located at the end of a large hydrophilic loop of the transporter. The transport protein may have a trimeric form as described for the Glt ph [42], with a concave aqueous basin in the middle facing towards the extracellular side (Fig. 8 B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The residues Cys-207 and Cys-210, which belong to a CXXC metal binding motif, are located at the end of a large hydrophilic loop of the transporter. The transport protein may have a trimeric form as described for the Glt ph [42], with a concave aqueous basin in the middle facing towards the extracellular side (Fig. 8 B).…”
Section: Discussionmentioning
confidence: 99%
“…8 B). Interestingly, ASCT2 contains a CXXC motif which is typical of metal binding sites in proteins [42]. The two cys residues (Cys-207 and Cys-210) of the motif, highlighted in dark grey (Fig.…”
Section: Page 11 Of 30mentioning
confidence: 99%
“…(Bayle et al, 1998) and the atkYB operon of Lactobacillus sakei (Stentz et al, 2000), do not have MerR-type helix-turnhelix regulators. In the cueAR region, a homologue of the recently published Streptococcus copZ regulator (Vats & Lee, 2001), copP, is present. However, the threegene operon in Streptococcus, namely copYAZ, encodes a regulator similar to that encoded by the copYZAB copper-transport system of Enterococcus -this regulator is not of the MerR type.…”
Section: Discussionmentioning
confidence: 99%
“…However, using transcriptional reporter gene fusions to the promoter of the atp operon, Quivey and colleagues found that the increase in F 1 F 0 -H/ATPase activity was correlated with increased transcription of the atp operon of S. mutans grown at low pH (Kuhnert et al, 2004 (Kakinuma, 1998;Magalhaes et al, 2005). For instance, the copYAZ operon in S. mutans encodes a Ptype ATPase responsible for transport of copper, allowing this organism to tolerate the high concentrations of copper potentially released from dental amalgam (Vats & Lee, 2001). pacL (SMU.1563), together with two other genes, SMU.1561 and SMU.1562, at the same locus, encodes a Ptype potassium transporter system.…”
Section: Upregulated Genesmentioning
confidence: 99%